PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI PENDIDIKAN AGAMA ISLAM BERBASIS ANDROID UNTUK KELAS 4 SEKOLAH DASAR - Roni Faturany; Umi Hayati; Fadhil Muhammad Basysyar (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The purpose of this study is to create an interactive learning medium based on Android. using Adobe flash cs6 to support learning in the current pandemic era. The development model used is the ADDIE model. There are four stages of the ADDIE development procedure, namely Analysis, Design, Development, Implementation, and Evaluation, this method is to produce and develop tested and empirical products. Lack of knowledge and use of technology makes elementary school students when doing learning from many who are lazy, causing a decrease in the achievement value of these students. So we need this Android-based interactive learning media to increase the spirit of learning in this pandemic era. This study aims to develop interactive learning media on Android-based Islamic religious education to keep students' values ??stable in Islamic religious education subjects. The results of this study are expected to be used by SD Negeri 2 Patuanan for learning media during the pandemic and continue to improve students to study hard. Keywords: Islamic religious education, Covid 19, Interactive Learning Media